Are laboratory tests useful for monitoring the activity of lupus nephritis? A 6-year prospective study in a cohort of 228 patients with lupus nephritis. Issue 2 (21st August 2008) - Moroni, G; Radice, A; Giammarresi, G; Quaglini, S; Gallelli, B; Leoni, A; Vecchi, M L; Messa, P; Sinico, R A
Abstract : Objectives: To evaluate the role of immunological tests for monitoring lupus nephritis (LN) activity. Methods: C3, C4, anti-dsDNA and anti-C1q antibodies were prospectively performed over 6 years in 228 patients with LN. Results: In membranous LN only anti-C1q antibodies differentiated proteinuric flares from quiescent disease (p = 0.02). However, in this group 46% of flares occurred with a normal value of anti-C1q antibodies versus 20% in proliferative LN (p = 0.02). In patients with antiphospholipid antibodies (APL), 33% of flares occurred with normal levels of anti-C1q antibodies versus 14.5% in patients that were APL-negative (p = 0.02). In proliferative LN, anti-C1q antibodies showed a slightly better sensitivity and specificity (80.5 and 71% respectively) than other tests for the diagnosis of renal flares. All four tests had good negative predictive value (NPV). At univariate analysis anti-C1q was the best renal flare predictor (p<0.0005). At multivariate analysis, the association of anti-C1q with C3 and C4 provided the best performance (p<0.0005, p<0.005, p<0.005 respectively). Conclusions: Anti-C1q is slightly better than the other tests to confirm the clinical activity of LN, particularly in patients with proliferative LN and in the absence of APL. All four "specific" tests had a good NPV, suggesting that, in the presence of normal values of each, active LN is unlikely.